2009
DOI: 10.1371/journal.pone.0006990
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin and Lipopolysaccharide Induce Platelet-Leukocyte Aggregates and Tissue Factor Release, a Thrombotic Mechanism in Hemolytic Uremic Syndrome

Abstract: BackgroundAggregates formed between leukocytes and platelets in the circulation lead to release of tissue factor (TF)–bearing microparticles contributing to a prothrombotic state. As enterohemorrhagic Escherichia coli (EHEC) may cause hemolytic uremic syndrome (HUS), in which microthrombi cause tissue damage, this study investigated whether the interaction between blood cells and EHEC virulence factors Shiga toxin (Stx) and lipopolysaccharide (LPS) led to release of TF.Methodology/Principal FindingsThe interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
168
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(178 citation statements)
references
References 55 publications
8
168
1
1
Order By: Relevance
“…Leukocyte-platelet complexes are larger in size and have been suggested to be susceptible for size-restricted microvascular trapping [27]. We observed that the number of leukocyte-platelet aggregates increased in septic mice, which is in line with previous studies showing increased generation of leukocyteplatelet complexes in inflammatory diseases [28][29][30]. Interestingly, we found that immunoneutralization of PSGL-1 completely inhibited sepsis-triggered formation leukocyteplatelet aggregates, which might help to explain the inhibitory effect of anti-PSGL-1 antibody on the accumulation of leukocytes in pulmonary capillaries in abdominal sepsis.…”
Section: Discussionsupporting
confidence: 91%
“…Leukocyte-platelet complexes are larger in size and have been suggested to be susceptible for size-restricted microvascular trapping [27]. We observed that the number of leukocyte-platelet aggregates increased in septic mice, which is in line with previous studies showing increased generation of leukocyteplatelet complexes in inflammatory diseases [28][29][30]. Interestingly, we found that immunoneutralization of PSGL-1 completely inhibited sepsis-triggered formation leukocyteplatelet aggregates, which might help to explain the inhibitory effect of anti-PSGL-1 antibody on the accumulation of leukocytes in pulmonary capillaries in abdominal sepsis.…”
Section: Discussionsupporting
confidence: 91%
“…Briefly, the seminal paper demonstrating for the first time such an interaction (18) was followed by a second paper (20) in which some of the authors reversed their position. However, we and other groups confirmed these findings in vitro and in patients (16,(21)(22)(23)(24)(25).…”
supporting
confidence: 87%
“…It has been shown that Stx2 added to human blood induced the formation of neutrophil/platelet or monocyte/platelet aggregates with activated thrombocytes and leukocytes, leading to the release of microvesicles (24,36). Complement activation on these complexes and on microvesicles should play a definite role in the development of HUS, because patients show higher platelet/leukocyte aggregates in blood with respect to healthy subjects (24,36).…”
Section: Inhibition Of the Formation Of Stx2-induced Neutrophil/platementioning
confidence: 99%
See 1 more Smart Citation
“…This in turn would contribute to endothelial damage and to further platelet activation leading to a positive feedback loop between platelets and monocytes, in which ROS and sCD40L stimulates each other. This represents a new pathogenic pathway mediated by monocyte-platelet interaction during HUS, that adds to the already described monocyte-platelet aggregate formation [51].…”
Section: Discussionmentioning
confidence: 60%